Informality and the Education Factor in Indonesian Labor - Axellina Muara Setyanti (Journal of Indonesian Applied Economics, 2020)
Informal sector plays a major role in Indonesia. In 2018, this sector generates 57,9 percent employment of the total workforce. Moreover, Small and Medium Enterprises (SMEs), one of the biggest pockets of informal workers account 64.19 million business units and contributes 99,99 percent to the total business units in Indonesia. Using the data from Survei Angkatan Kerja Nasional (Sakernas) 2018, this study aimed to identify the characteristics of informal workers in Indonesia and to understand does the informality vary across the workers’ education level. The results show that the higher of workers’ education, they are less likely to work in informal sector. Group of people who have higher probability to work informally are those who live in rural, women, elderly, have less household members, have primary to secondary education background, and not holding training certificate. The informal sector should get a particular attention from policy makers so it can improve working conditions to make better employment that offer greater economic inclusion, generate higher income, and create pathways out of poverty.